2005
DOI: 10.1177/088840640502800106
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Teachers' Knowledge, Opinions, and Educational Experiences with Attention Deficit/Hyperactivity Disorder

Abstract: The main purpose of this exploratory study was to investigate preschool teachers' past educational experiences, knowledge, and opinions related to ADHD. A second purpose was to determine if specific teacher variables (e.g., years of experience) were associated with higher knowledge of ADHD as measured by a criterion-referenced test. One hundred thirty-eight preschool teachers completed a questionnaire that included demographical information and questions related to knowledge and experiences with ADHD in presch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Compared to samples in which the majority reported journals to be their main source of information (14), this may reflect either courses being more commonly available in our country for preschool teachers, or a lower interest in reading articles about ADHD. If the former hypothesis is correct, this should be viewed as a significant opportunity to increase teachers' knowledge.…”
Section: Discussionmentioning
confidence: 78%
“…Compared to samples in which the majority reported journals to be their main source of information (14), this may reflect either courses being more commonly available in our country for preschool teachers, or a lower interest in reading articles about ADHD. If the former hypothesis is correct, this should be viewed as a significant opportunity to increase teachers' knowledge.…”
Section: Discussionmentioning
confidence: 78%
“…The question arises as to whether a teacher, who has obtained a more advanced level of education, consequently knows more about ADHD. A study [33] conducted in the United States, which aimed to investigate preschool teachers' past educational practices and their knowledge and understanding of ADHD, revealed that those teachers that obtained higher levels of academic training, such as a university education, performed on a superior level and obtained higher scores on the administered questionnaire than those teachers that only obtained a high school level of education.…”
Section: Teachers: a Pivotal Part Of The Eco-systemmentioning
confidence: 99%
“…However, research has also clearly documented that teachers in early childhood have reported they have knowledge of specific areas (i.e. ADHD) when assessments of their knowledge indicate otherwise [3]. Inservice opportunities should include pretests to help teachers become aware of misinformation and lack of information on specific topics.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…However, teachers of young children often have diverse educational backgrounds and experiences in teaching and working with young children (e.g. [3]). Furthermore, many teachers of young children have not been formally educated, which requires that they learn on the job and need training in different areas to learn how to support their classes.…”
Section: Introductionmentioning
confidence: 99%